Analysis of Cost Structure and Income of Trigona Sp. Honey Bee Farming in Payahe Village, Oba District, Tidore Islands City - Fatmawati, Mila; Mahmud, Haris; Kaddas, Fatmawati; Darwis, Herman (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
Honey bee business is included in the agribusiness sector industry that is able to produce honey, bee pollen and royal jelly products. One of the Trigona Sp honey bee business groups is the Molekat Mai Birahi Forest Farmer Group (KTH) located in Payahe Village, Oba District, Tidore Islands City. This study aims to: 1) analyze the cost structure of Trigona Sp honey bee cultivation business, 2) analyze the income of Trigona Sp honey bee cultivation business, 3) Analyze the level of B/C Ratio, Break Even Point (BEP) and Payback Period (PP). . Data collection methods in this study include interviews, observations and literature studies. The results of the study showed that the cost structure consisted of fixed costs in the form of depreciation of cages, protective clothing, honey suction tools, machetes and stup with a total of Rp 19,979,200 while variable costs of Rp 2,892,000 consisted of the cost of purchasing bottles, labels and purchasing colonies. The amount of income received per year is Rp 33,528,800. Meanwhile, the feasibility value of Trigona Sp honey bee business based on B/C Ratio is 1.5 while BEP analysis is 143 bottles with a value of Rp21,450,000 while the payback period payback period is 1.5 years. So that the Trigona Sp honey bee business is feasible. Better management is needed so that honey production is optimal and stable so that it can meet consumer demand.